Equações de velocidade crítica e hidráulica de escoamento superficial em canais de leito argiloso - ROCHA, Layane Carmem Arruda da (2020)
Better criteria to define the permissible flow velocity in cohesive channels still are necessary nowadays, in the hydraulic engineering linked to fluvial systems and to hydraulic projects under clayey beds. Most of the flow velocity equations were developed to sand beds, not considering the critical shear stress and cohesion from clayey beds. In this sense, with the objective to obtains a flow velocity equation to cohesive beds, dimensional analysis was applied to experimental data considering hydraulic variables and cohesive parameters that govern the concentrated flow velocity in these conditions. The experimental data were obtained in pre-formed channels in a cohesive bed constitute 60% clay proportion, and under increasing levels flow applied. The shear stress generated by applied flows weren't able to the critical shear stress of the cohesive bed channels (120 Pa), to significantly begin the detachment process on cohesive beds, due to channels high clay content. Based in Buckingham theorem the dimensional analysis developed a new equation to predict permissible flow velocity in clayey channels.